A Critical Discourse Analysis of some Persuasive Strategies of Ashton Carter’s 2016 Political Speech on Iraq and Syria Unrest - الساعاتي، نشوان مصطفى; إسحاق، رامي عيسى (جامعة الموصل - كلية الآداب, 2020)
يضم الخطاب السياسي بين جنباته سمات لابد أن يدركها المخاطبون، وينبغي أن يكون الخطاب مقنعاً لهم، وتهدف هذه الدراسة إلى تحليل ثلاثة أساليب إقناعيه خطابية في خطاب (أشتون كارتر) السياسي في عام ۲۰۱٦ حول الصراع في العراق وسوريا، فضلاً عن إيجاد الإيديولوجيات الضمنية في الخطاب. هذه الأساليب الخطابية هي التكرار والمجاز والمنطق الإقناعي، وإن النموذج المتبنّى لتحليل هذا الخطاب هو التحليل النقدي للخطاب لـ (ﭬان دايك) لعام ۲۰۰۰م، وتفترض هذه الدراسة أن يكون خطاب (كارتر) السياسي تعبيرياً عاطفياً ومنطقياً، وأنه مُصوّغ على أساس إيديولوجي، وقد توصلت هذه الدراسة إلى أن استراتيجية المنطق الإقناعي كانت الأكثر تكراراً والتي من خلالها التجئ (كارتر) للتحدث بالمنطق وسرد الحقائق لإقناع مستمعيه للانحياز إلى وجهة نظره. Political discourse contains features that should be understood by the audience, but it must fulfill the purpose of persuading the audience. This study examines three of Ashton Carter’s discourse strategies of persuasion in his 2016’s political speech on Iraq and Syria unrest, as well as the implicit ideologies. These discourse strategies are repetition, metaphor and appeal to logic. The model adopted to analyze the speech is critical discourse analysis under the impact of Van Dijk’s perspective. The study hypothesizes that Carter’s political speech is emotionally and logically expressive and that his speech is ideologically structured. The results have shown that Carter was so impressive in persuading his listeners due to the use of the three persuasive strategies. The results have also shown that the strategy of appeal to logic was the most frequent among others, through which he resorted to speaking logically and stating facts to make his listeners believe him and drive them at his stance.
Keywords: الخطاب السياسي -- الأساليب الإقناعية -- بلاغة الإقناع -- الصراعات السياسية -- العراق